POLA KEMITRAAN USAHATANI KEDELAI EDAMAME (Glycine max (L) Merr) ANTARA PETANI DENGAN PT. LUMBUNG PADI DI KABUPATEN GARUT - Carkum Cahyanto (FP, 2015)

(untitled)
The cooperation system edamame soybeans farming between farmers and PT. Lumbung Padi at Garut Regency. The aims of the research are to find out the cooperation between farmers and company, to analize the income and profit of the farmers, to find the feasibility of edamame soybeans, to realize the farmers perception to the company and to know the connection of farmers perception with the characteristic and revenue level of edamame soybeans farming. The respondents of this research are 50 farmers who having an associate with PT. Lumbung Padi. The data was gained by observation and interviewing method to farmers and corporate, then the data was analyzed descriptively. To find the feasibility of edamame soybeans, the data was analyzed by R/C Ratio, Profit Margin and Break Even Point (BEP), while to find the perception of farmers with cooperation is Arithmatic Mean. The correlation among variable is analyzed by correlation analysis rank spearmans in SPSS 15.0 Program. The result of this research show that the cooperation system which is applied between edamame farmers and PT. Lumbung Padi included the cooperation operational agribusiness system. Which is the company as the provider production tools seed and market, meanwhile farmer as the employee and land production provider. Farmer revenue is Rp 4.872.667,- and the profit is Rp 3.222.912,-. R/C Ratio and profit margin in edamame farm are 1,541 and 54, 10%. BEP of price and production are Rp 5.840, - and 662 kg. Farmer perceptions to company have a good category with score 3,621. The correlation between farmer perception and characteristic showed enough strong relations based on the age and employee in family, although with revenue the relations is weak. Keywords: edamame soybeans farming, partnership, feasibility, perception